Pre-emergent herbicide screening for wheat - Teixeira, Celso Augusto Sato (2024)
Weed control is a challenge in crop management due to the limited number of registered herbicides, especially for pre-emergent application. This study aimed to investigate the selectivity of pre-emergent herbicides with different mechanisms of action for wheat. The experiment consisted of two stages: the first involved screening under greenhouse conditions, and the second assessing the selected treatments under field conditions, with a focus on crop yield. Plant phytointoxication, crop stand, and shoot dry weight were assessed in the greenhouse experiment, and tillering, crop stand, plant height, canopy closure, yield, 1000-grain weight, and hectoliter weight in the field. Under greenhouse conditions, [imazapic + imazapyr], pendimethalin, isoxaflutole, florpyrauxifen, and halosulfuron-methyl produced the best results and were selected for the field experiment. Florpyrauxifen was the only herbicide that was selective both in greenhouse and field experiments. Isoxaflutole and trifluralin did not damage wheat in any of the field evaluations. Despite reducing crop performance in some assessments, pendimethalin and flumioxazin provided yield, hectoliter weight, and 1000-grain weight results equivalent to the herbicide-free control. Florpyrauxifen (1.08 g ha-1) was the most promising herbicide. Trifluralin (900 g ha-1), pendimethalin (1750 g ha-1), isoxaflutole (60 g ha-1), and flumioxazin (40 and 60 g ha-1) also produced grain yields equivalent to the control without herbicide.